2009
DOI: 10.1007/s10620-009-0847-8
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Significance of Perinuclear Anti-neutrophil Cytoplasmic Antibody in Korean Patients with Ulcerative Colitis

Abstract: Perinuclear anti-neutrophil cytoplasmic antibody (pANCA) is a serological marker associated with various immune-mediated diseases whose clinical significance and possible diagnostic roles in ulcerative colitis (UC) are still unclear. We aimed to evaluate the prevalence of pANCA expression and its association with clinical findings and disease course in Korean patients with UC. This study included 484 patients with UC who were diagnosed and treated between 1990 and 2006 at Severance Hospital, Yonsei University,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
2
10
0
3
Order By: Relevance
“…The prevalence of pANCA in Japanese,148 Korean,149 Thai,150 and Romanian151 patients with UC is lower compared with Caucasians, but comparable to Caucasian data in Mexico,152 Estonia,153 and a different Korean cohort 142. pANCA was found more frequently in UC patients with more extensive disease in China147 and Korea,149 with relapse rates higher when pANCA was present in the Korean cohort 149…”
Section: Ethnic Differences In Serological Antibodiessupporting
confidence: 54%
“…The prevalence of pANCA in Japanese,148 Korean,149 Thai,150 and Romanian151 patients with UC is lower compared with Caucasians, but comparable to Caucasian data in Mexico,152 Estonia,153 and a different Korean cohort 142. pANCA was found more frequently in UC patients with more extensive disease in China147 and Korea,149 with relapse rates higher when pANCA was present in the Korean cohort 149…”
Section: Ethnic Differences In Serological Antibodiessupporting
confidence: 54%
“…146,147 In contrast, studies from Korea reveal that it is 2.0-3.0% after one year and 3.3% after five to 15 years. 17,20 Furthermore, the author showed that there were no deaths associated with UC in that study, suggesting that Korean UC patients tend to have a milder form of the disease.…”
Section: Surgical Managementmentioning
confidence: 82%
“…A surgical approach is required for treatment of UC when there are life-threatening complications such as 20 • The cumulative colectomy rate is much lower in Korean UC patients than that in Western patients 17,20 • The rate of pouchitis after IPAA in Korean UC patients was similar to that in Western patients (37.5% vs 24-48%) 141 hemorrhage or perforation, and documented dysplasia or cancer. Other indications for surgery include fulminant colitis with or without toxic megacolon refractory to maximal medical management or intolerance to immunosuppression or medical therapy.…”
Section: Surgical Managementmentioning
confidence: 98%
See 2 more Smart Citations